Stability Indicating RP-HPLC Assessment and Stability Testing of Tazarotene and Halobetasol in Lotion Formulation - Gupta Tiruveedhi, V.L.N. Balaji; Battula, Venkateswara Rao; Bonige, Kishore Babu (Asian Journal of Chemistry, 2020)
A novel liquid chromatographic method was established and validated for the quantification of tazarotene and halobetasol in the presence of degradation products obtained during stress conditions. The liquid chromatographic method was based on isocratic elution on Knauer Eurospher II C18 (5 μm particle size, 250 mm × 4.5 mm) column using a mobile phase consisting of methanol, acetonitrile and 0.5 mM perchloric acid (40:45:15 v/v/v) mixture at flow rate of 0.9 mL/min. Quantization of tazarotene and halobetasol was done with UV detection at 234 nm. The method validity was assessed in agreement with the recommendations of the International Conference on Harmonization. Linearity, accuracy and precision were satisfactory over the concentration ranges of 2.25-13.5 and 0.5-3.0 μg/mL for tazarotene and halobetasol, respectively. Detection limit values of 0.006 μg/mL and 0.01 μg/mL were found for halobetsol and tazarotene, respectively, while the quantization limit values of 0.02 μg/mL and 0.033 μg/mL were found for halobetsol and tazarotene, respectively. The developed method is appropriate for routine analysis and quality control of tazarotene and halobetasol combination in lotion dosage form.